ANALISIS KUALITAS PELAYANAN DAN PENGARUHNYA TERHADAP KEPUASAN PELANGGAN - Mohammad Assegaff (Jurnal Ekonomi dan Bisnis, 2009)
The problems which are faced by Garuda’s Flight Company are the competitive of Garuda’sservices, under the industry standard of service quality, the low productivity of employee, andthe weak of information management. Moreover, the load factor, on time performing and operationalincome does not meet the target. The respondents are 150 persons and the samplingbased on the hair sample measures. The sampling method is random sampling, namely thatonly people who are chosen by the researcher will become respondent, not all people, andQuestioner is used as a method of collecting data. Method of data analyses used structuralequation modal program which is operated through AMOS Program. The outcome researchshow the following estimation parameter between reliance and service quality produce hassignificant influence. concern and service quality has significant influence, guarantee andservice quality has significant influence. empathy and service quality has significant influence,substances and service quality has significant influence. The last estimation of parameterbetween service quality and satisfaction product is also significant influence, in where hisresult also shows that hypothesis is acceptable. Based on the outcome research above, suggestionswill be given are: The Company has to keep accuracy both departing and arrivingtime, in addition, it should respond all complains from consumer, the rest, it ought to keep agood image on consumer.Keywords : Marketing, Service Quality, Satisfaction, Consumer